Nilai Moral Anak Usia Dini pada Kumpulan Fabel Persahabatan Karya Chandra Wening - Hidayat, Imam; Wardianto, Bayu Suta; Fauzi, Aziz (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2021)
Brawls between students that occur between students in educational institutions make the moral quality of students worse. Moral education can be done from an early age as a foundation for further education. One way is done with stories arranged in fables. This study aims to describe the moral values ​​contained in the Collection of Friendship Fables by Chandra Wening to be interpreted and taught to children. The research uses descriptive qualitative research methods. The object of this research is the stories contained in the Friendship Fable Collection. Data collection applies library techniques, listening techniques, and note-taking techniques. The data in the study were analyzed using content analysis techniques. The results showed that the moral values ​​contained in the Friendship Fable Collection by Chandra Wening consist of religious moral values ​​and social-moral values. Religious moral values ​​include patience and hard work. While social moral values ​​include: help, respect, and affection. This research contributes to understanding and practicing how moral education to everyday life from an early age.